PROBLEMS OF COUNTERACTION OF CRIME IN THE SPHERE OF INFORMATION TECHNOLOGIES (Journal of actual problems of jurisprudence, 2018)
With the growth in the volume of use of computer technologies and their significance in the lives of people in the world, a new type of crime in the field of information technology has appeared. The article is devoted to a detailed analysis of the emergence of crime in the field of information technology, as well as methods to combat this crime. The author reveals the rapid development for a short time of this type of crime in the field of information technology on the basis of a comparative analysis of the Republic of Kazakhstan with other countries. Special attention was paid by the author to stimulating factors to the emergence and consistent growth of crime in the field of information technology. The article problems of counteraction of crime in the sphere of information technologies are considered. The author comes to the greatest public danger is constituted by the crimes connected with illegal access to computer information. And also, on the basis of a comparative analysis of the Republic of Kazakhstan and other countries, the origin of this type of crime will be explained. Key words: crime, counteraction, information technologies, computer, information communications.